Unilateral Adie’s Tonic Pupil after Coronavirus Disease-19 (COVID-19): A Case Report: Unilateral Adie’s Tonic Pupil after Coronavirus Disease-19 (COVID-19): A Case Report - Nurul Hikmah; Mendy Candella (Majalah Oftalmologi Indonesia, 2022)
Introduction: Adie’s tonic pupil is a neuro ophthalmological disorder characterized by dilated pupil, which is unresponsive to light. It is caused by damage to postganglionic fibers of the parasympathetic innervation of the eye. Recent events of the coronavirus disease 2019 (COVID-19) pandemic had suggested that severe acute respiratory syndrome coronavirus-2 infection (SARS-CoV-2) had neurotropic and neuroinvasive capabilities. Purpose: To report a rare case of unilateral Adie’s tonic pupil after COVID-19. Methods: A single case report study. Case Report: A 31-year-old woman presented with a glare on the right eye 3 months ago. No other symptom was reported. No prior history of using any eye drops and trauma. Further investigation revealed a history of asymptomatic SARS CoV-2 infection. Her best-corrected visual acuity of both eyes was 1.0, but we observed an impairment of accommodation on the right eye. A fixed dilated right pupil, 8 mm in diameter, was observed without any constriction on near reflex. Slit lamp and funduscopy examination were within normal limits on both eyes. Pilocarpine 0.1% test was positive on the right eye. Neurological examinations and brain imaging was within normal limits. The patient was diagnosed with Adie’s tonic pupil. She was treated with pilocarpine 0.1% once daily. After 2 months of follow up, her complaint of glare was diminished but no improvement of near acuity was seen on the right eye. Conclusions: This case report was one of the first few cases of Adie’s tonic pupil possibly associated with COVID-19.